Application of Arabic Conversational Vocabulary Text to Improve Maharah Kalam at SMK Tahfidzul Qur'an: Penerapan Teks Kosa Kata Percakapan Bahasa Arab Untuk Meningkatkan Maharah Kalam di SMK Tahfidzul Qur’an - Zainuri; Wahyudi, Imam (STAI Nurul Huda Kapongan Situbondo, 2023)
The language of Arabic is a very important language in communicating both locally and internationally. A method is highly recommended to be applied in the development of Arabic language learning, especially Arabic language learning at the madrasah level. This study aims to improve students' vocabulary and conversation skills and this research uses qualitative methods because this research focuses on the implementation of Arabic language learning, namely maharah kalam using conversation methods. The results of learning using the application of vocabulary texts in improving students' maharah kalam, and students who are very capable of reaching 30% and who are able to reach 57% and who are less capable 13% and these results are known from the research process of student conversation results using Arabic. So that it can be concluded that the learning results of the application of this conversational vocabulary text can improve students' maharah kalam